POTENSI Bacillus spp. DARI RIZOSFER TANAMAN AKASIA SEBAGAI AGENS HAYATI Fusarium sp. DAN PEMACU PERTUMBUHAN TANAMAN - Anderson, Radika Sabrina; Marwan, Husda; Mulyati, Sri (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2025)
ABSTRACT Acacia crassicarpa is a promising species for the wood processing industry, with productivity reaching 110.2 m³/ha at four years of age. However, seedling production in nurseries often faces disease problems, particularly infections by Fusarium sp., which can lead to significant economic losses. Biological control using antagonistic microbes, such as Bacillus spp., offers an effective and environmentally friendly alternative. This study aimed to explore the potential of Bacillus spp. isolated from the rhizosphere of A. crassicarpa as a biocontrol agent against Fusarium sp. and as a plant growth promoter. A total of 32 Bacillus spp. isolates were obtained, with 21 isolates exhibiting antagonistic activity against Fusarium sp. in vitro. The BAM-18 isolate showed the highest inhibition rate at 43.00%. Several isolates, including BAM-18 and BAM-21, also demonstrated chitinolytic activity, nitrogen fixation, phosphate solubilization, and potassium solubilization, indicating their potential to support plant growth. Keywords : Acacia crassicarpa, Bacillus spp., Rhizosphere, Biological control.